The mask of Zorro - Campbell, Martin; Eskow, John.; Elliott, Ted.; Rossio, Terry; Jahnson, Randall; Claybourne, Doug.; Foster, David, 1929-; Banderas, Antonio; Hopkins, Anthony, 1937-; Zeta-Jones, Catherine, 1969-; Tri-Star Pictures; Amblin Entertainment (Firm); et al. (Culver City, CA : Columbia TriStar Home Video, 1998)
The elder Zorro comes out of retirement to train a new Zorro to fight the enemy Montero.
Rated PG-13.
Originally released as motion picture.
"This film has been modified from its original version. It has been formatted to fit this screen."
Director of photography, Phil Meheux ; film editor, Thom Noble ; music, James Horner.
Antonio Banderas, Anthony Hopkins, Catherine Zeta-Jones, Stuart Wilson, Matt Letscher.
VHS, Dolby surround.
Keywords: Feature films; Zorro films; Adventure films; Video recordings for the hearing impaired